TREPS, a tool for coordinate and time transformations in space physics. (January 2018) - Génot, V.; Renard, B.; Dufourg, N.; Bouchemit, M.; Lormant, N.; Beigbeder, L.; Popescu, D.; Toniutti, J.-P.; André, N.; Pitout, F.; Jacquey, C.; Cecconi, B.; et al.
Abstract: We present TREPS (Transformation de REpères en Physique Spatiale) an online tool to perform coordinate transformations commonly used in planetology and heliophysics. It is based on SPICE kernels developed by NASA/NAIF. Its usage is straightforward, with a 4-step process, including various import/export options. Interoperability with external services is available through Virtual Observatory technology which is illustrated in a use case. Highlights: Light-weight online software to provide spatial coordinate transformations in planetary science and heliophysics. Based on NAIF/SPICE kernels. Uses Virtual Observatory technology to ease interoperability with other tools and databases.